Konstruksi Pemikiran Hukum Islam Organisasi Muhammadiyah dan Nahdlatul Ulama - Ikhsan, Muh; Sultan, Lomba; A, Azman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the Islamic legal thinking of the two largest Islamic mass organizations in Indonesia, namely Muhammadiyah and Nahdlatul Ulama. Muhammadiyah’s Islamic legal thinking is modernist in nature, emphasizing rational ijtihad based on the Qur’an and Sunnah and making modern science a consideration in carrying out transformation and establishing law through the Majelis Tarjih and Tajdid forum. Meanwhile, Nahdlatul Ulama is more traditional in nature, emphasizing the importance of preserving the classical fiqh treasury (turats) through the qauli and manhāji methods in the Bahtsul Masa'il forum. By using a literature study approach method by examining relevant data sources, this study found that Muhammadiyah and Nahdlatul Ulama have different constructions and patterns of Islamic legal thinking, but have the same orientation, namely realizing Islamic law that is able to adapt, dialogue and respond to the challenges of the times. In addition, the diversity of approaches of both of them is an intellectual wealth and a treasure of Indonesian Islam that is relevant to answering the challenges of the times.